Experimental and Numerical Study of Process Limits for Deep Drawing of Dome-Structured Sheet Metals - Dengiz, C.G.; Yildizli, K. (Springer London, 2017)
The demand for lightweight materials is increasing due to energy saving in the sheet metal forming industry. Structured sheet metals are a strong yet lightweight material. But the process limits for deep drawing of structured sheet metals should be investigated for the forming process. In this study, the stiffness properties and the process limits of dome-structured duplex stainless steel (DSS) were determined experimentally by three-point bending test and Erichsen test, respectively. Also, the Erichsen test was simulated using ABAQUS. Firstly, the forming limit diagram (FLD) of DSS was determined. After that, the dome structures, which had diameters of 3, 6, and 9 mm, were stamped on planar DSS sheet metal. The bending test results showed that the bending strength of 6- and 9-mm dome-structured sheet metal was two times higher than planar and 3-mm dome-structured sheet metal. After the dome stamping process, the 3- and 6-mm dome-structured sheet metal still had a process safety margin of 58 and 47%, respectively, for uniaxial tension in the FLD. On the other hand, the 9-mm dome-structured sheet metal had a process safety margin of 57% for biaxial tension in the FLD. © 2017, Springer-Verlag London.
Keywords: Deep Drawing; Dome Structure; Duplex Stainless Steel; Erichsen Test; Structured Sheet Metal